Filarial Lymphatic Pathology Reflects Augmented Toll-Like Receptor-Mediated, Mitogen-Activated Protein Kinase-Mediated Proinflammatory Cytokine Production - Babu, Subash (American Society for Microbiology, 2011)

(untitled)
Lymphatic filariasis can be associated with the development of serious pathology in the form of lymphedema, hydrocele, and elephantiasis in a subset of infected patients. Toll-like receptors (TLRs) are thought to play a major role in the development of filarial pathology. To elucidate the role of TLRs in the development of lymphatic pathology, we examined cytokine responses to different Toll ligands in patients with chronic lymphatic pathology (CP), infected patients with subclinical pathology (INF), and uninfected, endemic-normal (EN) individuals. TLR2, -7, and -9 ligands induced significantly elevated production of Th1 and other proinflammatory cytokines in CP patients in comparison to both INF and EN patients. TLR adaptor expression was not significantly different among the groups; however, both TLR2 and TLR9 ligands induced significantly higher levels of phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 mitogen-activated protein (MAP) kinases (MAPK) as well as increased activation of NF-κB in CP individuals. Pharmacologic inhibition of both ERK1/2 and p38 MAP kinase pathways resulted in significantly diminished production of proinflammatory cytokines in CP individuals. Our data, therefore, strongly suggest an important role for TLR2- and TLR9-mediated proinflammatory cytokine induction and activation of both the MAPK and NF-κB pathways in the development of pathology in human lymphatic filariasis.